Perbandingan Hukum Internasional Dan Nasional Tentang Hak Asasi Manusia - Muhammad Fadli Efendi (Fakultas Hukum Universitas Islam Malang, 2022)
Human rights are rights that must be upheld, guaranteed and protected by law, the state, the government and other human beings. It cannot be reduced, revoked, or even eliminated, because these rights are inherent in humans from the moment they were created (baby in the womb). Cases of human rights violations in the world are so rife in various countries, even rarely that countries do not violate human rights. So it is necessary to make an improvement effort in protecting and guaranteeing human rights. This study aims to provide a complete understanding of human rights through normative juridical research methods with a statutory, comparative, and historical approach. From this research, it is found that there are visible differences ranging from the definition of human rights, mechanisms for resolving human rights violations, to institutions for resolving human rights violations both in international of law and national of law in Indonesia.